Get the answers you need at Westonci.ca, where our expert community is dedicated to providing you with accurate information. Get immediate and reliable answers to your questions from a community of experienced experts on our platform. Join our platform to connect with experts ready to provide precise answers to your questions in different areas.

To solve the equation x ^2 - 2x = 3 by the technique of completing the square, you would add 4 to each side of the equation as one of the steps to reaching the solution.

Sagot :

Answer:

x = -1

x = 3

Step-by-step explanation:

[tex]\sf x^2 - 2x = 3[/tex]

Add 1 to both sides:

[tex]\sf \implies x^2 - 2x+1 = 3+1[/tex]

Factor the left side:

[tex]\sf \implies (x-1)^2 = 4[/tex]

Square root both sides:

[tex]\sf \implies x-1 = \pm2[/tex]

Therefore:

[tex]\sf \implies x-1=-2 \implies x=-1[/tex]

[tex]\sf \implies x-1=2 \implies x=3[/tex]